2006
DOI: 10.1128/aem.72.4.2721-2729.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preculturing Conditions on Lag Time and Specific Growth Rate of Enterobacter sakazakii in Reconstituted Powdered Infant Formula

Abstract: Enterobacter sakazakii can be present, although in low levels, in dry powdered infant formulae, and it has been linked to cases of meningitis in neonates, especially those born prematurely. In order to prevent illness, product contamination at manufacture and during preparation, as well as growth after reconstitution, must be minimized by appropriate control measures. In this publication, several determinants of the growth of E. sakazakii in reconstituted infant formula are reported. The following key growth p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 17 publications
4
31
1
1
Order By: Relevance
“…Large amounts of powdered substitutes for breast milk should be obtained from different sources to be analyzed for the presence of this bacterium 78 . It has been suggested that thermal treatment of rehydrated PIF may be a practical way of minimizing neonatal risk to C. sakazakii infection [79][80][81] . Simmons et al has recommended using refrigeration and limiting hang time to prevent or retard the growth of C. sakazakii 5 .…”
Section: Risks and Hazards Controlmentioning
confidence: 99%
“…Large amounts of powdered substitutes for breast milk should be obtained from different sources to be analyzed for the presence of this bacterium 78 . It has been suggested that thermal treatment of rehydrated PIF may be a practical way of minimizing neonatal risk to C. sakazakii infection [79][80][81] . Simmons et al has recommended using refrigeration and limiting hang time to prevent or retard the growth of C. sakazakii 5 .…”
Section: Risks and Hazards Controlmentioning
confidence: 99%
“…This corresponds to a final concentration of 10 4 CFU ml Ϫ1 after preenrichment of the sample in buffered peptone water (BPW) (CM0509; Oxoid AG, Pratteln, Switzerland). The level of competitive flora in PIF is generally low (8), the lag time for desiccated cells to recover after rehydration of PIF at 37°C has been estimated as 0.254 h (15), and the approximate doubling time at 37°C in infant formula for Cronobacter spp. is 20 min (10).…”
mentioning
confidence: 99%
“…These parameters can be determined using different techniques. Plate counting can be used to generate the data points max and by fitting of the growth curve (15,33). Often, automated optical density (OD) measurements are used to determine parameters for growth as they allow quicker data generation with less need for human resources (22).…”
mentioning
confidence: 99%